Lab-on-a-Book: A Paper-Based Chemistry Kit for Hands-on Science Learning in Under-Resourced Schools (Constructionism Conference Proceedings, 2025)
This paper presents Lab-on-a-Book, a low-cost, paper-based chemistry kit designed to support hands-on science learning for middle school students (ages 11–14) in under-resourced schools. The kit integrates scientific experiments directly onto the pages of a book, replacing traditional laboratory materials with paper-based alternatives. Using a constructionist approach, it engages students in active inquiry and problem-solving. Each experiment is framed around students’ own questions, encouraging exploration, collaboration, and iterative learning. The book includes eleven experiments covering fundamental chemistry concepts such as pH, density, and mixtures. This paper discusses the theoretical foundations and design elements of Lab-on-a-Book, highlighting its potential to promote science learning in resource-constrained settings.